2012
DOI: 10.1037/a0027420
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making styles and stress.

Abstract: This study analyzed the relationship between each of five decision-making styles, including Rational, Intuitive, Dependent, Avoidant, and Spontaneous (Scott & Bruce, 1995) and two indicators of stress, Perceived stress and Sleep quality, among administrative officers and investigators at three Swedish public authorities: The National Tax board, the Social Insurance agency, and the Police authority (n ϭ 472). Results showed that Avoidant style and, to some extent, the Dependent style were significantly associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 19 publications
(26 reference statements)
1
28
0
11
Order By: Relevance
“…The sample was a convenience sample, which imposes limitations on generalizing these results for the broader population. Furthermore, it would be convenient to adapt the GDMSI to specific contexts, such as clinical, legal, military, economic, and political contexts, which have been shown to have specific relations among different decision-making styles and constructs such as stress or anxiety (e.g., Allwood & Salo, 2012;Thunholm, 2008) in order to obtain evidence of the predominant styles in such contexts. Also, further research can identify the relationships among the decision-making styles and affective states or specific emotions (Reyna et al, 2013) and contribute to understanding the role of emotions in the decision-making process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample was a convenience sample, which imposes limitations on generalizing these results for the broader population. Furthermore, it would be convenient to adapt the GDMSI to specific contexts, such as clinical, legal, military, economic, and political contexts, which have been shown to have specific relations among different decision-making styles and constructs such as stress or anxiety (e.g., Allwood & Salo, 2012;Thunholm, 2008) in order to obtain evidence of the predominant styles in such contexts. Also, further research can identify the relationships among the decision-making styles and affective states or specific emotions (Reyna et al, 2013) and contribute to understanding the role of emotions in the decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…and may allow for the analysis of the relationship among the decision-making styles and other constructs. In this regard, it has been observed that avoidant and dependent styles are positively correlated with the self-reported ratings of stress (e.g., Allwood & Salo, 2012;Salo & Allwood, 2011); and that rational and avoidant styles are positively correlated with anxiety and depression (Schoemaker, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Findings revealed that the avoidant style was strongly related to stress, as decision makers appeared to avoid making decisions because they found it more stressful. In the same vein, Allwood and Salo (2012) investigated the relations between decision-making styles and stress in the organisational work context. Results suggested that certain styles, particularly avoidant and to some extent dependent style, were associated with higher stress.…”
Section: Burnout and Decision-making Stylementioning
confidence: 99%
“…O estilo dependente apareceu como um bom preditor de planejamento, contrariando estudos de Rubinton (1980), Salo e Allwood (2011) e Allwood e Salo (2012). Os resultados demonstram a importância associada ao contato com o outro e com a troca de informações para o planejamento da aposentadoria.…”
Section: Discussão Geralunclassified
“…Pesquisas utilizam os estilos de decisão para entender diferentes fenômenos, como estresse (Allwood & Salo, 2012), satisfação com a vida e autoestima baseada na performance (Salo & Allwood, 2011) e liderança (Hariri, Monypenny, & Prideaux, 2013). Os resultados dos trabalhos citados apontam a relação entre o estilo racional e variáveis positivas (como menos estresse, maior satisfação com a vida e maiores níveis de liderança), enquanto os estilos dependente e evitativo se relacionam com variáveis mais negativas (como maior percepção de estresse e menor qualidade de sono, menor satisfação com a vida e menor liderança).…”
unclassified